CONSERVING AND UTILIZING NATURAL RESOURCES CREATIVITY BASED ON BIODIVERSITY AND COMMUNITY PARTICIPATION IN MAE RAM WATERSHED, CHIANG MAI - Kunpradid, Tatporn; Joradol, Atinut; Samphutthanont, Ratchaphon; Hanmuangjai, Wacharee; Tagun, Rungnapa; Cheenacharoen, Saran; Chaimongkhon, Phitsanuphakhin; Deethae, Aomhatai; Supahan, Nattida; Leelahakriengkrai, Pongpan (Life Sciences and Environment Journal, 2024)
This study explores water management in the Mae Ram Watershed, Chiang Mai, focusing on the interplay between local community practices and water resources, guided by the Sufficiency Economic Concept and indigenous knowledge. Extensive data collection, including participation in field surveys and sampling, was conducted, incorporating secondary data in the upstream, middle, and downstream areas of the watershed. The examination involved local community management and stakeholders, covering the diversity and distribution of various biological and land-use aspects, as well as the current environmental situation. The results showed that almost the entire area consisted of deciduous dipterocarp forest, with low plant abundance, except for an evergreen forest area upstream. Key findings revealed the influence of physical factors on vegetation's spatial distribution and seasonality. Higher terrains exhibited denser plant life, and steeper slopes had more vegetation. The study identified 88 plant species collaborating with fungi, lichens, algae, insects, and birds. The Natural resource utilization in the upstream and middle streams depended on local indigenous, traditional, and ethnic beliefs, whereas downstream areas were primarily used for agriculture and residence. Water quality in the Mae Ram upstream was clean, while it was moderate in the middle and downstream areas, based on physical-chemical parameters and biological indicators. The water balance of all villages was sufficient, while some villages were facing a shortage period in the dry season. The community involvement in water resource management varied from moderate to high; however, overall, local self-management needed to be more robust, necessitating external collaboration. The watershed needs a consistent annual plan and ongoing community participation in water resource protection and conservation.